A Critical Assessment Of Textbooks For Middle Eastern History - Allen, Calvin (Teaching History: A Journal of Methods, 1996)
At the 1995 meeting of the Middle East Studies Association a group of colleagues and I were sitting around a table consuming a variety of beverages and discussing, of all things, textbooks. Predictably, there was not consensus, especially as one of the group was the author of a text and each of us had a slightly different approach to our courses that rendered one text mere useful than another. Three points of general agreement emerged and all are predictable: no text was perfect, there are several good texts available, and there are also some texts that are not recommended.